A Low Power 32 Bit CMOS ROM Using A Novel ATD Circuit - Siddhant Kukreti; Gurmohan Singh; Vemu Sulochana (Institute of Advanced Engineering and Science, 2013)
A low power high speed 32 Bit ROM circuit implemented on 0.18µm CMOS process has been presented in this paper. The circuit is build using a parallel ROM core structure and runs on 1.8 V supply voltage. A novel Address Transition Decoder (ATD) circuit is proposed which energizes the ROM components such as Row Decoder, Column Decoder, ROM core etc, for short time intervals when there is a transition in input address bits. The power consumed in ROM with proposed ATD circuit is 0.78 mW, which corresponds to 82.27% reduction in power as compared to ROM without ATD circuit (4.46 mW). At the output almost full signal swing has been achieved without using any sense amplifier. The implemented ROM has a very low latency of 0.56 ns.DOI:http://dx.doi.org/10.11591/ijece.v3i4.3165